Biogenic silver nanoparticles incorporated hydrogel beads for anticancer and antibacterial activities - Vyshnavi T. Veetil; Vidhu Jayakrishnan; Vaisakh Aravindan; Anakha D. Rajeeve; Sreekanth Koolath; Ramasamy Yamuna (Scientific Reports)
Abstract Green nanotechnology is an effective treatment approach being used in cancer research with less adverse effects. This work describes the incorporation of silver nanoparticles synthesized from clitoria ternatea plant extract (Ag@CT NPs) into sodium alginate and gelatin polymer blends (SA/GEL) to produce Ag@CT-SA/GEL polymer beads using calcium chloride (CaCl2) crosslinking agent. Both the formation and the effective incorporation of Ag@CT NPs into polymer blend have been proven by various spectroscopic analysis, surface morphology study and energy dispersive X-ray analysis. Ag@CT NPs and Ag@CT-SA/GEL demonstrate good antibacterial and antioxidant activities comparable to commercially available drug. Dimethyl thiazolyl tetrazolium bromide (MTT) anticancer assay and apoptosis study of plant extract and Ag@CT NPs against lung cancer cell lines clearly indicate that Ag@CT-SA/GEL polymer bead can serve as an effective anticancer agent.